Editorial - Löfström, Jan; Sandahl, Johan; Szukala, Andrea (sowi-online e.V., 2025)
In this autumn issue of the JSSE, we are pleased to present five original articles. These contributions deal with social science education in different contexts and from different educational settings, reminding the reader of the heterogeneity of our common research field. Two of the articles deal with teacher training, two with considerations and understandings of teachers and one focusing on young peoples’ understanding of social issues. However, the similarities in the research contributions are also evident. All of the articles focus on the importance of inclusive, critical and balanced social science education in different ways and with different outsets. In times when democracy and human rights are being contested, it is important to highlight the role of democratic and civic education and what it can contribute with.